The Unsubmissive Islands: Children’s Memories During the Cold War / (An)Archive: Childhood, Memory, and Cold War (Mnemo ZIN, Eds.) - Chmiel, Fira (Journal of Childhood Studies, 2024)
This book review aims to provide a broad reflection on (An)Archive: Childhood, Memory, and Cold War, highlighting its theoretical and methodological relevance for the study of past childhoods and childhood studies in general. It emphasizes the innovative approach of creating an alternative public archive, as well as the compelling focus on constructing collective memories through biographical narratives situated in various geographies and time periods influenced by the Cold War.